(untitled) (Indian Journal of Arid Horticulture, 2025)
One of the mosl impommt things in successful vegetable transplant production is LO grow s1mng and healt.hy tmnsplants. The role of plant growing media is become important in modulating physiological responses that will evenmally le.ad to producing high quality seedlings. Aim of this study was to evaluate tomato (Lycopersicou esculenwm Mm.) and 1ra11spla111 growth in various soiJless growing media. Sc::ven growing media were formt1hued using peat moss and cocopeat as the organic components and perlite as the inorganic components. To facilitate interpretations, seedling height. Stem diarnc.::ter. num\>t!r of tf\1e lc;:aves, elaLivc.:: Jc;:.af d1lorophyll conh;nt, stem fresh weight. SI.cm dry weight, root fresh weight. and root dry weight of 6-week old transplant grown in different growing media were compared. The results of the Sll1dy have shown that the use of differc.nt growing medja h_ighly affected growth and quality of tomato transplant